Frameworks for sustainable development in the city of Gothenburg - A case study of sustainability frameworks and indicators within the area of the built environment - Dahlgren Camacho, Carolina; Simonsen, Frida (My University, 2020)
The aim of this thesis was to examine the perceptions of using frameworks and indicators, such as Agenda 2030, for sustainable development within the area of the built environment, in the City of Gothenburg. The opinions of the interviewed stakeholders varied with regards to the need of using Agenda 2030 and the Sustainable Development Goals (SDGs) locally. Several interviewees meant that the municipality has an extensive amount of programs, and that Agenda 2030 should not be handled in a separate program. Therefore, it seemed to be preferred that the SDGs should be integrated in existing programs, or in financial control documents. Further, findings from literature showed that there is a lack of knowledge regarding sustainable development indicators (SDIs), and their impact on policy-making and to have better outcomes. However, a local adoption of Agenda 2030 requires adaptation of the global targets and indicators, to increase the relevance of the targets in local sustainability reporting and policy-making. All private companies included in this study were seen to have adopted Agenda 2030 for their operations. One of the reasons was by the authors suggested to depend on that organizations less complex than the municipal organization, face minor difficulties in the implementation, since they in comparison are less obliged to adopt the whole set of goals. Considering that studies have shown that the municipality already has strong steering towards sustainability, another implemented sustainability framework may be perceived as needless by politicians in the City Council and Committees. Conclusion regarding the research question, about defining the sustainable city, was that especially concrete targets and indicators are needed, else various actors involved with the built environment, will not follow the same desired path towards the sustainably built city. Furthermore, we the authors argue that SDG 11, in comparison to the national environmental quality goal 15 - god bebyggd miljö (a good built environment), better answer the question regarding the ’sustainably built city’. Furthermore, SDIs are needed as they provide guidance. There are some important things to consider when using indicators, such as that they are reflections of human values and never purely objective, that not everything is meaningful to measure, and that indicators purposed to assess sustainable development must be followed for a long time.
Keywords: Agenda 2030, SDG 11, mål 15 - god bebyggd miljö, sustainable cities, sustainable development indicators, indicators, Gothenburg, building sector, built environment